UTILISATION OF GIS TECHNOLOGY FOR TOURISM MANAGEMENT IN VICTORIA ISLAND LAGOS - Ofobruku Sylvester Abomeh; Onabanjo Bankole Nuga; Iheabunike Okafor Blessing C. (European Scientific Journal, ESJ, 2013)
﻿This study covers tourism destinations which include beach, Museums, Parks and resorts, hotels, restaurants, clubs, bars, cinemas and fitness centres, as well as complementing tourism destination Services which includes police post, clinics and hospital in Victoria Island Lagos and how the utilisation of GIS technology can be use to improved tourism management. Also to model accessibility to these points of interest mentioned above using Geographic information system analytical tools and functions. Geographic coordinates of the location of all bars, clubs, restaurants, cinema, fitness centre, hospital, clinic, police post and various tourists destination have been picked with their corresponding attributes to build a database using Arc Map 9.3 software package Geo database. Analyses to aid decision for management and future planning was carried out using the spatial statistical tools in the GIS application used for this study. The analysis included central Feature analysis which was used to model area central to Tourism Facilities, Tourism services and Tourisms Destinations in Victoria Island.